2021
DOI: 10.22437/ppd.v8i6.10891
|View full text |Cite
|
Sign up to set email alerts
|

Financial development and tourism at the traditional village in Gianyar, Bali: Tri Hita Karana Value

Abstract: Tri Hita Karana (THK) is the foundation and guide of the general Hinduism society in living their life. This study aims to identify THK integration on the synergy Village Credit Institution (LPD) and traditional village and observe the LPD contribution in the financial and tourism development at the traditional village in Gianyar, Bali. An ethnography approach was used to identify the problem. The result found that THK has a substantial role in the existence of LPD, which contributes to the traditional village… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
0
1
0
Order By: Relevance
“…The financial supervisor was included as regional income. The results of previous studies found that to support the development of the tourism sector, sound financial management was needed to obtain funds for the development of tourist destinations (Suidarma et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The financial supervisor was included as regional income. The results of previous studies found that to support the development of the tourism sector, sound financial management was needed to obtain funds for the development of tourist destinations (Suidarma et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…By documenting and sharing the outcomes of this community service initiative through this journal manuscript, we hope to contribute to the existing body of knowledge on community-driven tourism development and financial management. Furthermore, we aim to inspire other researchers, practitioners, and policymakers to recognize the significance of financial management in ensuring the sustainability and success of Village-Owned Enterprises in the tourism sector (Hyshchuk, 2021;Latif et al, 2023;Rukmiyati et al, 2023;Suidarma et al, 2021).…”
Section: Introductionmentioning
confidence: 99%